BLACK IS BEAUTIFUL: Konstruksi Kemewahan dan Eksotisisme dalam Iklan Kopi Kapal Api - Yusuf, Rizaldy (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2014)
This research is based on the construction of signs which often used in advertising to convey message. Therefore, this research is conducted to see how the construction of signs representing myth of lifestyle in Kapal Api Special coffee advertising, “Suka Yang Hitam”version. This research uses Roland Barthes’ semiotics theory as main theory, supported by three approaches of representation theory, and Fiske’s representation theory. The method used in this research is Barthes’ semiotics with denotative, conotative, and myth as the devices. The primary data in this research is text of ad and supported with secondary data, which is the result of an interview with advertising practitioner, media and advertising culturalist, and audiences. To test the data validity, this research uses source triangulation. The main results of this research are: denotatively, Kapal Api Special coffee advertising, “Suka Yang Hitam” version only shows the brand advantages. However, in the scope of conotative, this ad shows luxurious lifestyle shifting the meaning of coffee drinking to be something that can increase social status. This ad represents myth of luxury as a modern lifestyle which is influenced by western culture ideology. Based on these findings, it will be better if the effect of this ad to audiences and other in line marketing communication tools is analyzed in the future research.